(untitled) (Bangladesh Journal of Medical Science, 2010)
Objective: The present study was undertaken to assess the level of knowledge and practice about tetanus toxoid immunization of a group students from a public university. Materials & Methods: This cross-sectional survey was carried out on 113 female students randomly selected from Dhaka University. The interview was conducted using a structured questionnaire. Results: Mean age of the respondents was 19.7±1.2 years (mean±SD). About 90% of the respondents knew about tetanus. Regarding age groups prone to develop tetanus, 49% respondents told ‘children <1 year’, 26.5% ‘neonate’, 14.7% ‘children of 1-5 years’, 3.9% ‘children of 6-12 years’, 5.8% ‘women of 15 years and above’. Respondents showed lack of knowledge about the target group for TT vaccination. None has mentioned about the necessity of TT immunization before the start of reproductive life. Regarding number of dose for complete vaccination 60% respondents mentioned ‘five’, 10.9% ‘three’ and 4.9% ‘two’. Twenty two percent (22.1%) of the respondents did not know. Over one-third (34.5%) of the respondents was found to be completely immunized, 24.8% on schedule, 17.7% incompletely immunized and 23% was not at all immunized. Respondents’ source of knowledge about TT immunization was TV in 35% cases followed by health workers 24%, newspaper 16%, radio and other sources 25%. Among the nonvaccinated group 50% respondents told of their unawareness about need for vaccination against tetanus before the start of their reproductive life, 15.4% told about lack of information regarding of place and time of vaccination and 19.6% complained about inconvenience schedule and place of vaccination. Conclusions: More than two-thirds of the respondents had knowledge about tetanus toxoid immunization before the start of their reproductive life but only half of them were completely vaccinated. Mass media found to be the main source of information. So planners and policy-makers should utilize mass medium and gear up the activities of health workers to convey the correct massages regarding tetanus toxoid immunization to its clients. Key words: Female reproductive life; tetanus; TT immunization Knowledge; vaccination age. DOI: 10.3329/bjms.v8i4.4707 Bangladesh Journal of Medical Sciences Vol.8(4); October 2009 pp102-109